A Meta-Analysis of Vascular Endothelial Growth Factor for Nasopharyngeal Cancer Prognosis - Wang, Feng; Peng, Lisha; Wang, Yong; Liu, Xiaodong (Frontiers in Oncology, 2018)
BACKGROUND Vascular endothelial growth factor (VEGF) has been reported to serve as a promising prognostic marker in several cancers. This meta-analysis aims to assess the prognostic significance of VEGF in nasopharyngeal cancer (NPC). METHODS We conducted a systematic literature search of PubMed, Embase and Cochrane Library for observational studies published until June, 2018 to identify observational studies on the prognostic effect of tissue VEGF expression or serum VEGF level on the survival of NPC. The primary outcome measure assessed was overall survival (OS). The secondary outcomes included disease-free survival (DFS) or progression-free survival (PFS). Summary hazard ratio (HR) and their 95% confidence interval (95% CI) were derived using a random-effects model. RESULTS Out of 840 retrieved citations, 16 studies inclusive of 1345 patients were included in the analysis of tissue VEGF expression and cancer survival. The pooled HRs for OS and DFS in patients with high VEGF expression were 2.07 (95% CI: 1.32 to 3.25) and 5.99 (95% CI: 2.66 to 13.48), respectively, with significant heterogeneity between studies (I2= 79.1% for OS and 50.2% for DFS). Tissue high VEGF expression was not significant associated with short RFS, PFS or MFS. Five studies also investigated the prognostic effect between serum VEGF level and patient survival and found that high serum VEGF level was significantly associated with short OS for patients with NPC (HR 2.47, 95% CI 1.16 to 5.28), but not with short PFS (HR 1.47, 95% CI 0.92 to 2.35). CONCLUSIONS Determination of tissue VEGF expression and serum VEGF level have the potential to serve as biomarkers and add prognostic information in NPC. Prospective analyses of associated data on VEGF expression and serum VEGF level in large PNC cohorts are urgently required to advance our understanding of the relationship between VEGF and PNC outcomes.